Large sensory analysis of vegetables from conventional, organic and no-till practices - S. Loustau; F. Lefer; S. Ducos (Journal of Agriculture and Food Research)
There is a growing interest in agriculture to address soil deterioration issues and achieve a sus-tainable agrosystem. Many producers introduce no-till techniques and show significant yields with better ecosystem functioning, as well as improved carbon and water cycles. However, sensory analysis to compare vegetables from these practices are scarce. In this paper, we conduct triangle and hedonic tests over 15 panels of consumers for a total of 915 consumers. Based on statistical hypothesis testing and maximum likelihood estimation, significant statistical differences (p < 0.05 and less) are produced for both triangle tests and hedonic ranking in some specific cases. These results show a trend for sensory preferences of no-till practices.